Highly‐Safe and Ultra‐Stable All‐Flexible Gel Polymer Lithium Ion Batteries Aiming for Scalable Applications. Issue 21 (20th April 2020) - Shen, Wei; Li, Ke; Lv, Yangyang; Xu, Tao; Wei, Di; Liu, Zhongfan
Abstract: With the development of flexible electronics, flexible lithium ion batteries (LIBs) have received great attention. Previously, almost all reported flexible components had shortcomings related to poor mechanical flexibility, low energy density, and poor safety, which led to the failure of scalable applications. This study demonstrates a fully flexible lithium ion battery using LiCoO2 as the cathode, Li4 Ti5 O12 as the anode, and graphene film as the flexible current collector. The graphene oxide modified gel polymer electrolyte exhibits higher ionic conductivity than a conventional liquid electrolyte and improves the safety of the flexible battery. The optimum design of the flexible graphene battery exhibits super electrochemical performance, with a 2.3 V output voltage plateau and a satisfactory capacity of 143.0 mAh g −1 at 1 C. The mass energy density and power density are both ≈1.4 times higher than a standard electrode using metal foils as current collectors. No capacity loss is observed after 100 thousand cycles of mechanical bending. More importantly, even in the clipping state, this flexible gel polymer battery can still demonstrate a stable and safe electrochemical performance. This work may lead to a promising strategy of high‐performance scalable LIBs for the next‐generation flexible electronics. Abstract : An extremely safe and all‐flexible lithium ion battery is designed by using ultra‐thin graphene film as a current collector and a graphene oxide modified poly(vinylidene fluoride‐tri‐fluoroethylene‐chlorofluoroethylene) based gel polymer electrolyte. At 100 thousand times mechanical bending or even in the clipping state, this flexible gel polymer battery can still generate a stable and safe electrochemical performance.